Illicit Love: History and Sexuality in the Theater of Roberto Ramos Perea (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
This paper studies the historical drama titled Por maricón (Convict of Buggery or Crimes Against Nature) written by Puerto Rican playwright, Roberto Ramos Perea, in 2016. Although the title of the work in Spanish may seem rather provocative and borderline offensive, Por maricón was the name given to a colonial court case that occurred on the Island of Puerto Rico in 1842, in which a young biracial man of both African and European descent was accused of committing sodomy with a Spanish military corporal. Ramos Perea’s work recreates the places, events, and characters surrounding this court case, urging his public to reconsider notions of race, gender, sexuality, power, and colonialism. Drawing upon the theories of Judith Butler and the concept of intersectionality developed by Kimberlé Crenshaw, this essay examines the implications of such representations as depicted in Ramos Perea’s play. I will discuss creative ways in which this dramatic work can be implemented within a university level course by utilizing theater practices developed by Rosa Luisa Márquez. Such practices promote the genre of drama as an effective pedagogical tool used to develop interpersonal skills and explore the humanities.